Foam concrete and compositions and methods of forming same
By using limestone calcined low-carbon materials such as clay cement (LC3) and waste engine oil (UEO), foam concrete compositions are formed, which solves the problem of reduced stability of traditional foam concrete during solidification and hardening, and achieves faster solidification, higher stability and lower carbon emissions.
Patent Information
- Application Number
- CN202411326794.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-28
AI Technical Summary
The foam bubble compression and deformation of existing foam concrete during solidification and hardening leads to reduced stability, and the carbon-intensive properties and long solidification times of traditional cements are not conducive to foam stability.
Limestone calcined clay cement (LC3) and waste engine oil (UEO) are used as foam stabilizers and sustainable cement. By mixing LC3, UEO, foaming agent and water, a foam concrete composition is formed to reduce carbon emissions and improve foam stability.
Faster solidification time and higher foam stability of foam concrete are achieved, reducing carbon emissions, and improving the sustainability and thermal insulation properties of building materials.
Smart Images

Figure CN119707426A_ABST
Abstract
Description
[0001] This application claims priority to U.S. Patent Application No. 63 / 585,848, filed on September 27, 2023, the contents of which are incorporated herein by reference in their entirety as if fully set forth herein. Background of the Invention
[0003] The construction industry is a major contributor to CO2 production as it is responsible for 25% to 38% of global greenhouse gas emissions. Within this industry, cement manufacturing and heating / cooling for building construction are the main causes of CO2 emissions, accounting for 6.9% and 6% of global emissions, respectively. Given its large carbon contribution, achieving carbon neutrality by 2050 remains an important milestone for the construction industry. Decarbonization of the construction industry encompasses the efforts made worldwide to provide a sustainable built environment with minimal CO2 emissions. Among these efforts, the innovation of low-carbon and energy-efficient building materials can have significant environmental benefits in achieving long-term decarbonization in nature. The use of such materials can reduce carbon emissions in the material production process (e.g., the calcination process in cement production) and improve the energy efficiency of buildings. Therefore, the strategic selection of sustainable materials makes a significant contribution to the broad efforts to achieve global carbon neutrality.
[0004] Foamed concrete (also known as "lightweight foamed concrete", "lightweight cellular concrete" (LCC), and "low-density cellular concrete" (LDCC)) shows great potential in decarbonizing the construction industry due to its life cycle carbon emission reduction properties covering material use, manufacturing process, and service phase. As a low-density material, foamed concrete requires less raw materials and energy for transportation and production, thereby reducing carbon emissions. In addition, the manufacturing process of foamed concrete reduces carbon emissions by approximately 50% compared to traditional concrete, which provides a practical solution for reducing the carbon footprint of the construction industry. In addition, the excellent thermal insulation properties of foamed concrete make it particularly advantageous during the service phase of a building, where it generates significant energy savings. Specifically, its thermal insulation capabilities help maintain indoor temperature stability and reduce the energy required for heating and cooling, resulting in reduced carbon emissions throughout the service life of the building. The life cycle carbon emission reduction properties of foamed concrete make it a promising option for decarbonizing the construction industry.
[0005] Although foamed concrete has great potential for carbon reduction, maintaining the structural stability of the foam before the concrete solidifies is key to its successful manufacture and implementation. Stability refers to the ability of the foam liquid film to maintain its structural independence, thereby avoiding degradation phenomena such as bubble coarsening, foam drainage and rupture. In order to solve the common instability problems of widely used surfactant-based foaming agents, foam stabilizers or gas-liquid interface modifiers have been used to extend the foam life and enhance stability. The working principle of foam stabilizers is to enhance the expansion viscoelasticity of the foaming liquid film, resulting in a thickened Plateau boundary, as shown by scanning electron microscopy (SEM). This thickened boundary strengthens the resistance of the foam to gas diffusion and mechanical stress in the foam film, resulting in foam stabilization and the production of the final foamed concrete with desired mechanical, thermal and acoustic insulation properties. Current foam stabilizers (mainly nanomaterials, polymer chains and surfactant monomers) have shown good stability performance. However, their industrial-scale application is facing some challenges. For example, nanomaterials and polymer chains are expensive to produce, limiting their widespread use, while surfactant monomers, while cheaper and more readily available, may not provide the same stability.
[0006] In addition to foam stabilizers, the choice of cement for foamed concrete is also crucial to enhancing its foam stability. Conventional ordinary Portland cement (OPC) has a long setting time, which has a negative impact on foam stability. In particular, during the setting and hardening of concrete, foam bubbles are compressed and deformed, causing the foam to disappear. In addition, the cement hydration process depletes the free water required to maintain the integrity of the foam, making it more likely to disappear. In addition to technical issues, the use of carbon-intensive OPC also raises environmental issues. Therefore, in order to achieve stable foaming and improve the sustainability of foamed concrete products, it is crucial to find low-carbon cementitious materials with shortened setting times.
[0007] It is therefore an object of the present invention to provide a foamed concrete composition, a foamed concrete, a method of forming a foamed concrete composition and a method of forming foamed concrete in which at least one of the above disadvantages is alleviated or at least to provide a useful alternative to the artisan and the public. Summary of the invention
[0008] According to a first aspect of the present invention, a foamed concrete composition is provided, wherein the foamed concrete composition comprises limestone calcined clay cement (LC 3 ), waste engine oil (UEO), foaming agent and water.
[0009] According to a second aspect of the present invention, there is provided a foamed concrete formed by a foamed concrete composition, wherein the foamed concrete composition comprises limestone calcined clay cement (LC 3 ), waste engine oil (UEO), foaming agent and water.
[0010] According to a third aspect of the present invention, there is provided a method for forming a foamed concrete composition, the method comprising: 3 ), waste engine oil (UEO), foaming agent and water are mixed.
[0011] According to a fourth aspect of the present invention, there is provided a method for forming foamed concrete, the method comprising forming a foamed concrete composition, comprising: 3 ), waste engine oil (UEO), foaming agent and water are mixed. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings, in which:
[0013] FIG. 1( a ) shows the structural formulas of components of used engine oil (UEO) that can be used in the present invention;
[0014] FIG. 1( b ) shows the structural formula of the components of the blowing agent that can be used in the present invention;
[0015] Figure 2(a) to Figure 2(c) Schematic diagram of forming a UEO-enhanced lightweight LC according to an embodiment of the present invention 3 Methods of foamed concrete;
[0016] FIG3( a ) shows an apparatus for conducting a foam volume test;
[0017] FIG3( b ) shows an electron microscope suitable for performing foam microscopy experiments;
[0018] FIG3( c ) shows an apparatus for performing a compressive strength test;
[0019] FIG3( d ) shows the apparatus used to perform SEM analysis;
[0020] FIG3( e ) shows the apparatus used to conduct the thermal conductivity test;
[0021] FIG3( f ) shows a device for conducting a macro thermal insulation test;
[0022] Figure 4(a) shows the foam volume evolution over time;
[0023] FIG4( b ) shows the height evaluation of the foam volume, where Tt represents the onset of foam disappearance, thus marking the transition between state I and state II;
[0024] Figure 4(c) shows the correlation between Tt and UEO dose level;
[0025] Figure 4(d) shows the correlation between the remaining foam fraction and the UEO dosage level;
[0026] FIG5( a ) shows a microscopic photograph of a foam mixture without UEO at the foam surface;
[0027] FIG5( b ) shows a microscopic photograph of a foam mixture with 1 wt % UEO;
[0028] FIG5( c ) shows a microscopic photograph of a foam mixture with 2 wt % UEO;
[0029] FIG5( d ) shows a magnified microscopic photograph of the foam mixture without UEO;
[0030] FIG5( e ) shows a magnified microscopic photograph of a foam mixture having 1 wt % UEO;
[0031] FIG5( f ) shows a magnified microscopic photograph of a foam mixture having 2 wt % UEO;
[0032] Figure 5(g) shows the change in foam size with increasing amount of UEO additive;
[0033] FIG5(h) shows the relevant gas-liquid interface changes in the present invention;
[0034] Figure 6(a) shows the compressive strength of foamed concrete with different UEO dosages;
[0035] FIG6( b ) shows the change in compressive strength of the foamed concrete according to the present invention compared to the reference foamed concrete;
[0036] FIG7( a ) is a thermal image of the initial stage of the reference foamed concrete without UEO;
[0037] FIG7( b ) is a thermal image of the reference foamed concrete of FIG7( a ) after a two-hour conditioning period;
[0038] FIG7( c ) shows the evolution of the temperature at points 1 and 2 over time for the reference foam concrete of FIG7( a );
[0039] FIG7( d ) is a thermal image of the initial stage of the foamed concrete incorporating 1 wt % UEO;
[0040] FIG. 7( e ) is a thermal image of the foamed concrete of FIG. 7( d ) with 1 wt % UEO after a two hour conditioning period;
[0041] FIG7( f ) shows the evolution of the temperature over time at points 1 and 2 for the foamed concrete with 1 wt % UEO of FIG7( d );
[0042] Fig. 7(g) is a thermal image of normal concrete with the same water-to-cement ratio as foamed concrete at the initial stage;
[0043] FIG7( h ) is a thermal image of the plain concrete of FIG7( g ) after a two-hour conditioning period;
[0044] FIG7( i ) shows the evolution of the temperature over time at points 1 and 2 for the plain concrete of FIG7( g );
[0045] Figure 8(a) shows pores of various sizes in sample U0;
[0046] Figure 8(b) shows pores with more uniform sizes in sample U10;
[0047] Figure 8(c) shows the pores with larger sizes in sample U20;
[0048] Figure 8(d) shows fine and sharp ettringite crystals along the pore boundaries in sample U0;
[0049] Figure 8(e) shows the long and wide ettringite crystals in sample U10;
[0050] Figure 8(f) shows the elongated ettringite crystals in sample U20;
[0051] Figure 8(g) shows the porous microstructure in sample U0;
[0052] FIG8(h) shows the densely packed microstructure in sample U10; and
[0053] Figure 8(i) shows the macropores in sample U20. DETAILED DESCRIPTION
[0054] Typically, "used engine oil" ("UEO") includes engine oil that has been used in various transportation vehicle engines, such as automobiles, private cars, and heavy-duty vehicles, for a period of time that is typically greater than six months. During this period of time, the density of UEO tends to fall into a unique range that is typically lower than the density of new engine oil. This density variation reflects operational wear, component breakdown, and the introduction of contaminants, such as wear particles (including metal wear debris, soot, and sludge) and other impurities (such as dust, water, and oxidation products).
[0055] It has been found that waste engine oil (UEO), which is an abundant municipal and industrial waste, has become a potential alternative to conventional foam stabilizers due to its high viscosity and large hydrocarbon chains. Specifically, the aggregated and viscous UEO molecules can increase the viscosity of the foam fluid against seepage and coalescence, thereby strengthening the Plateau boundary against mechanical stress. It is reported that the distribution of the oil phase within the foam structure strengthens the foam film and thickens the Plateau boundary. In addition, the interwoven network structure of UEO can limit the mobility of water molecules in the bubble channel, thereby reducing the cross-section of the liquid foam channel. In addition, the active sulfonic acid groups in UEO help it to plasticize the fresh cement mixture, thereby ensuring foam uniformity and producing a strong boundary and a refined pore structure around the pores. Therefore, UEO is considered to have great potential as an effective foam stabilizer. However, exceeding the UEO dosage threshold may lead to defoaming behavior and foam disappearance due to the threshold dosage effect. The present invention is based on the research results on the feasibility and appropriate dosage of UEO in the production of foamed concrete, thereby promoting the conversion of waste to resources.
[0056] On the other hand, limestone calcined clay cement (“LC 3 ”) (which is a blend of clinker, limestone and calcined clay) offers a lower carbon, faster setting alternative to ordinary Portland cement (OPC). LC 3 The use of clinker is reduced and due to the lower process temperature, its production process emits less carbon dioxide. 3 It emits approximately 30%-50% less CO2 per ton of cement produced, making it a sustainable alternative to OPC. 3 Sets faster, typically within six hours compared to seven hours for OPC; this improves foam stability and reduces the likelihood of foam collapse. This increased setting speed also improves production efficiency by enabling faster curing times and shorter construction cycles. Therefore, the use of LC in foam concrete production is 3 It is an efficient and sustainable solution to improve the performance of foam concrete and reduce the carbon footprint of OPC production.
[0057] The present invention aims to improve the foam stability and sustainability of foamed concrete, thereby contributing to the deep decarbonization of the construction industry. A low-carbon, waste-enhanced low-density LC has been envisioned. 3 Foamed concrete, including UEO and LC 3They are used as foam stabilizers and sustainable cement for waste conversion, respectively. The technical feasibility of such foam concrete is verified by evaluating key performance indicators including foam stability, compressive strength and thermal insulation coefficient. The underlying mechanisms driving the performance changes are revealed through microscopic techniques, which help to elucidate foam properties such as boundary thickness, foam size and pore system within concrete.
[0058] The materials used to produce low-carbon foamed concrete include UEO, LC 3 , a foaming agent and water (such as tap water). The UEO used was from Chevron Corporation. Gold Ultra SAE 15W-40, a multi-grade heavy-duty diesel engine oil designed for a variety of engines. This UEO (which is six months old and has a density of 0.848 g / cm 3 ) is obtained from the engine used for the generator. Usually, the density of 0.6-2.0g / cm 3 As shown in Figure 1(a), UEO mainly contains long-chain alkanes (15-30 carbon atoms) and cycloalkanes with side chain lengths up to 20 carbons, while there are minor components of aromatic components with benzene rings and saturated side chains.
[0059] The foaming agent may have a foaming ratio of 1:30 to 1:50. The foaming ratio refers to the volume of foam produced per unit volume of the foaming agent solution. For example, a foaming ratio of 1:30 means that 1 unit volume of the foaming agent solution will produce 30 unit volumes of foam. The foaming agent used was GCP Applied Technologies Inc. AE S45 foam concentrate, the foam concentrate is composed of sodium dodecyl sulfate (SDS) and alcohol ether sulfate (AES), as shown in Figure 1 (b). According to the user manual, Darex AE S45 concentrate is premixed with water at a ratio of 1:40 parts by weight to obtain a density of about 65 kg / m 3 LC 3 The blend consists of 50 wt% Type I ordinary Portland cement, 30 wt% metakaolin (calcined kaolin clay), 15 wt% limestone and 5 wt% gypsum. 3 The proportions of the components in the blend can be adjusted by as little as 5% to optimize the properties of the foamed concrete while maintaining blend integrity and effectiveness.
[0060] Table 1 shows the LC 3 Physical properties and oxide composition.
[0061] Table 1LC 3 Physical properties and oxide compositions of blends.
[0062]
[0063] Note: - represents a negligible value.
[0064] Table 2 shows the design mix of low carbon foamed concrete according to the present invention. The specific water to cement (w / c) weight ratio, fresh density and UEO additive amount are determined as follows. The foamed concrete according to the present invention generally has a w / c weight ratio in the range of 0.3 to 0.6. A lower w / c weight ratio will result in a dry and hard mixture and foam collapse during mixing, while foamed concrete with a high w / c weight ratio lacks the strength to hold the bubbles, resulting in segregation. Therefore, in order to maintain foam stability and long-term concrete durability, a balanced w / c weight ratio of 0.45 was selected. A 620 kg / m 3 The new density is estimated to be 600 kg / m 3 The dry density of foam concrete used as lightweight building insulation material is usually 400kg / m 3 With 800kg / m 3 The dosage of foam stabilizer for foamed concrete usually varies from 0.5 wt% to 2 wt% of the foam produced. In order to investigate the optimal UEO dosage that can be incorporated into foamed concrete without compromising the foam stability, the UEO addition level was set to 0, 0.5 wt%, 1 wt%, 1.5 wt% and 2 wt% (all relative to the weight of the foam produced) in the corresponding foamed concrete samples U0, U05, U10, U15 and U20.
[0065] Table 2 Design mix proportions of foamed concrete with and without UEO (kg / m 3 )
[0066]
[0067] After the material preparation, the manufacturing process of the foamed concrete composition and the foamed concrete according to the present invention is started, such as Figure 2(a) to Figure 2(c) shown.
[0068] As shown in FIG2(a), a foaming agent 10 is blended / mixed with a dilute solution of water 12 (such as tap water) and UEO 14. The mixture is then stirred for 5 minutes at 700 rpm, for example, with a handheld electric stirrer 16 to produce a UEO enhanced foam mixture 18.
[0069] Separately, LC 3Cement 20 is mixed with water 12 (such as tap water); the mixture is then stirred for 5 minutes, for example by a hand-held electric mixer 22, to obtain a well-mixed cement paste 24, as shown in Figure 2(b).
[0070] As shown in FIG. 2( c ), the UEO-enhanced foam mixture 18 is mixed with the cement slurry mixture 24, and the mixture is blended until no visible traces of white foam remain, indicating a homogenous UEO-enhanced cement slurry mixture 26. The resulting UEO-enhanced cement slurry mixture 26 is then carefully poured into a steel mold and allowed to cure for one day for proper cement hardening to form a UEO-enhanced foam concrete 28. During the curing process, a plastic foil 27 is applied to cover the mold opening to prevent overheating and moisture loss. Alternatively, aluminum foil may be used instead. Although plastic film is commonly used to cover the mold during the initial curing process to prevent moisture loss, aluminum foil may also be used for the same purpose, such as when a higher degree of insulation is required to regulate the curing temperature.
[0071] The stability of the prepared UEO-enhanced foam mixture 18 is characterized by the initial foam volume and its seepage rate over time. Immediately after preparation, the foam 18 is poured into a 250-mL graduated cylinder 30 standing on a stable support 32 (such as a table). As shown in Figure 3 (a), the volume of the bottom liquid is recorded over 120 minutes by a device 34 with video recording capabilities (such as a smartphone), which is fixed relative to the support 32 by a holder 36. Specifically, the foam seepage is calculated as the recorded volume divided by 250 mL, multiplied by 100%.
[0072] The microstructural properties of the freshly prepared UEO-enhanced foam mixture 18, such as the foam size and the thickness of the Plateau boundary, are analyzed by a digital imaging solution at room temperature using an electron microscope 38 (e.g., Nikon SMZ800N), as shown in FIG3( b). The process begins by depositing a drop of the UEO-enhanced foam mixture 18 onto a microscope slide 40 using a pipette. A cover glass is then applied to minimize damage to the mixture structure and prevent the formation of bubbles. The prepared slide 40 is examined under a microscope 38 to study its microstructural features and capture corresponding images.
[0073] The compressive strength of the foamed concrete 28 was evaluated by performing a compression test at a loading speed of 1.7 kN / s using a universal testing machine 42 until failure, as specified by ASTM C109 and as shown in Fig. 3(c). The average of the values from three test specimens was taken as the ultimate compressive strength.
[0074] After the above test, the fragments of cement paste sample 28a were collected to prepare SEM samples to evaluate the microstructural properties of foamed concrete 28. In order to prevent cement hydration, sample 28a was soaked in isopropanol for 24 hours and then dried at 55°C for three days using a vacuum pump to eliminate residual moisture. The treated sample 28a was then fixed to a conductive adhesive and gold sputtered via an SC7620 mini sputter coater for high-resolution imaging. As shown in Figure 3 (d), a ZEISS Sigma 300 microscope 44 was used for SEM analysis, which was operated at an accelerating voltage of 3 kV with a magnification range of 10-1,000,000 in a selected area. Microscopic images were quantitatively analyzed using ImageJ software with a Fiji plug-in.
[0075] The thermal performance of the foamed concrete 28 was evaluated by a thermal conductivity test as shown in FIG. 3( e ) and a macroscopic thermal insulation test as shown in FIG. 3( f ). According to EN ISO 22007-2, a Hot Disk TPS2500S thermal constant analyzer with a thermal sensor 46 was used to test the thermal conductivity of a concrete sample 28a having a size of 50 mm×50 mm×25 mm. Prior to the test, the sample 28a was heated in an oven at 55° C. for 72 hours to achieve a constant weight, thereby minimizing the effect of moisture on the measurement accuracy. During the measurement, the sensor 46 was placed between two pieces of the sample 28a, thereby ensuring that the flat side was in contact with the sensor 46. Three random locations on the sample 28a were selected for testing. In order to intuitively evaluate the thermal insulation capability of the foamed concrete 28, a hot plate test apparatus with a heater 48 was set up to detect the side surface temperature of the sample 28a using an infrared thermal imager 50.
[0076] The effect of UEO on foam stability was evaluated from the perspective of changes in foam volume, critical onset of foam disappearance, and residual foam fraction. Figure 4(a) to Figure 4(d)The details are shown in Figure 4(a). Specifically, Figure 4(a) provides an overall depiction of the time-varying foam volume assessment, in which it is found that the foam volume decreases with the passage of time. As shown in Figure 4(b), the foam percolation behavior can be divided into two different regimes, labeled I and II. This division is consistent with the behavior observed in the foam system integrated with ultra-high-chaotropic nanoparticles. In regime I, the foam volume undergoes a rapid decline, which is attributed to the gravity-driven liquid percolation process. Interestingly, a stable period was observed in the foam with 1 wt% UEO (i.e., 1% of the total weight of the foam produced), which indicates that the foam state has reached temporary stability. During this stage, the liquid percolation rate is minimized, and the foam bubbles show self-similar growth due to the Ostwald ripening and coalescence of the bubbles. After this stage, the foam transitions to regime II, indicating that the foam enters the advanced age, in which a significant disappearance is observed. The onset of foam disappearance between regimes I and II is represented by Tt. To demonstrate the effect of UEO dosage on Tt, Figure 4(c) quantitatively depicts the correlation between UEO dosage and Tt. Clearly, the foam injected with 1 wt% UEO exhibits the longest Tt, lasting 35 minutes, compared to the pure foam with a Tt of 20 minutes. Increasing the UEO dosage to an optimal level exceeding 1 wt% (i.e., 1% of the total weight of the foam produced), such as from 1.5 wt% to 2 wt% (all relative to the total weight of the foam produced) results in a reduction in the Tt value from 15 minutes to 10 minutes. In addition to evaluating the critical Tt value, the relationship between the remaining foam fraction and the UEO dosage level is also shown in Figure 4(d). It is noteworthy that the foam with 1 wt% UEO retained the largest remaining foam fraction, i.e., 32%, during the 120-minute measurement period. In contrast, the foam containing 2 wt% UEO showed a lower remaining foam fraction of 21%, which contrasts with the foam without UEO, which maintained a fraction of 23%. Together, these measurements indicate that an appropriate UEO dosage (specifically 1 wt%) promotes foam stabilization. However, increasing the UEO dosage beyond this optimal threshold resulted in decreased foam stability.
[0077] The stability of foams is closely related to their microstructural characteristics. In order to uncover the hidden mechanisms leading to the altered stability of foams containing UEO, the foam changes in structure and size were investigated at the microscopic level, such as Figure 5(a) to Figure 5(h)As shown. It is noteworthy that the UEO-reinforced foam shows a unique black appearance in Figures 5(b) and 5(c) compared to the pure foam shown in Figures 5(a) and 5(d). This means that UEO is absorbed onto the gas-liquid interface, thereby promoting the formation of a thicker and more solid interfacial film within the foam, as shown in Figure 5(e). Specifically, at millimolar concentrations, UEO is used to stabilize the nonionic surfactant foam by generating electrostatic repulsion between the foam film interface, thereby forming a thicker and uniformly sized foam film. This strong film helps to enhance the strength of the liquid film and improve the resistance to bubble deformation in the foam. In addition to the change in film thickness, a significant change in film size was observed with increasing UEO concentration. It is noteworthy that the pure foam synthesized without UEO exhibits a larger size, an inhomogeneous structure of about 195 microns, as shown in Figure 5(g). In contrast, including UEO at a concentration of 1 wt% results in a reduction in foam size, resulting in a more uniform structure, which was measured to be between 100 and 110 microns, as shown in Figure 5(g). The appearance of small and uniform bubbles can be attributed to the dispersing effect of UEO. In addition, the integration of UEO promotes surface charging in the foam, including electrostatic repulsion between relative interfaces. Therefore, the thickened gas-liquid interface helps to achieve an extended self-growth life in state I and enhances shape stability. However, too high UEO concentration will induce agglomeration, thereby imposing significant self-weight on the foam structure and causing the foam structure to be unstable, as shown in Figure 5(h). Similar concentration-dependent foam stability has been observed in other foam stabilizers (such as non-clays and Keggin ions). These findings clearly show that foam stability depends on the level of UEO addition. Specifically, the optimal dose of UEO brings uniform structural size and thicker structural boundaries to the foam, which ultimately contributes to enhanced foam stability.
[0078] To assess the practicality of using UEO-enhanced foam to make foamed concrete, the effect of the original synthetic foam on the macroscopic properties (i.e., compressive strength and thermal insulation) of foamed concrete 28 was studied. These parameters are critical considering the intended application of foamed concrete as an insulating material for walls, roofs, and floors.
[0079] First, the compressive strength of the developed foamed concrete with different UEO dosage levels was compared with the compressive strength of the reference foamed concrete without UEO; the comparison results are shown in Figure 6(a) and Figure 6(b). In the formula in Figure 6(b), f i and f R Denote the compressive strength of concrete with and without UEO, respectively. Change Δ f is through (f i -f R ) / 3f RSum and multiply by 100% to determine. In these UEO-enhanced foamed concrete systems, when the UEO addition level is limited to less than 2 wt%, the compressive strength shows an increase relative to the reference sample. In particular, the foamed concrete containing 1 wt% UEO (named U10) shows a maximum increase of about 15% at a compressive strength of 2.3 MPa. As explained in the previous discussion, this enhancement can be attributed to the formation of a uniform foam structure facilitated by the presence of UEO. The uniform UEO-enhanced foam forms a homogeneous matrix in the foamed concrete, which is characterized by an optimized pore filling mode, thereby enhancing its mechanical properties. However, when the UEO addition level exceeds 1 wt%, a significant decrease in the compressive strength of the foamed concrete is observed. This reduced compressive strength can be attributed to UEO agglomeration, which is caused by its excessive addition. These poorly dispersed UEO particles in liquid form occupy certain parts of the foamed concrete, ultimately resulting in an unhydrated and uneven cement matrix. These harmful internal phase compositions within the foamed concrete lead to a weakening of its compressive strength. The above observations and interpretations indicate that incorporation of 1 wt% UEO is optimal for improving the compressive strength of foamed concrete, whereas 2 wt% UEO addition is ideal for maximizing the UEO recycling potential. In addition, it is noteworthy that the technical feasibility of upcycling UEO in foamed concrete production has been confirmed, considering the observed enhancement in the compressive strength of foamed concrete.
[0080] In addition to the compressive strength, the thermal conductivity of the developed foamed concrete was compared with the reference concrete, and the results are listed in Table 3. Relative to the reference foamed concrete sample without UEO, the thermal conductivity decreased by 1.75% and 12.8% with the incorporation of 0.5 wt% and 1 wt% UEO, respectively. It is worth noting that the concrete sample with 1 wt% UEO exhibited the lowest thermal conductivity of 0.162 W·m -1 K -1 , which was reduced by about 16% compared to the reference sample. This reduction can be attributed to the formation of uniform pores in the foamed concrete facilitated by UEO as a foam stabilizer. These uniform pores are a beneficial pore structure feature in foamed concrete as they retard heat loss and improve thermal insulation performance. In addition, due to the presence of sulfonic acid groups, UEO confers additional advantages by acting as a dispersant, which further enhances the uniformity of the foam structure. However, when the UEO addition level exceeds 1 wt.%, the thermal conductivity coefficient increases. This increase may be associated with the agglomeration of UEO particles, resulting in a poorly dispersed internal structure in the foamed concrete, which promotes heat transfer and reduces its thermal insulation performance. These findings suggest that upgrading UEO in foamed concrete can enhance its thermal insulation properties, thereby helping to save energy and mitigate greenhouse gas emissions in green buildings.
[0081] Table 3 Thermal conductivity of foamed concrete with and without UEO
[0082]
[0083] To directly visualize the UEO-enhanced lightweight LC 3 The effectiveness of the foam concrete 28 as a thermal barrier was investigated by using an infrared thermal imaging camera to map the temperature distribution of the foam concrete 28, such as Figure 7(a) to Figure 7(i) As shown. It is noteworthy that during the two-hour heat penetration period, the foamed concrete U10 recorded the lowest temperatures at points 1 and 2, which were 20.0°C and 22.9°C, respectively, as shown in Figures 7(a) and 7(b). In contrast, the reference concrete without UEO recorded higher temperatures at the equivalent points, which were 22.1°C and 24.6°C, respectively, as shown in Figures 7(d) and 7(e). In addition, in Figure 7(c), the foamed concrete U10 exhibited a temperature difference of about 4°C between points 1 and 2; this is greater than the temperature difference of the reference sample, which was approximately 3°C, as shown in Figure 7(f). These temperature changes indicate that the incorporation of an appropriate amount of UEO can effectively prevent the penetration of external heat sources and thereby enhance the thermal insulation properties of foamed concrete.
[0084] To further demonstrate the advantages of foamed concrete over ordinary concrete, the temperature changes of ordinary concrete slabs were also measured. It is worth noting that the temperature on the surface of the ordinary concrete slab in Figures 7(g) and 7(h) is significantly higher than the surface temperature of the foamed concrete. After a two-hour heat penetration period, the temperature values at points 1 and 2 were recorded as 26°C and 31.4°C, respectively. These temperature values are significantly higher than those of the optimal foamed concrete U10, indicating that ordinary concrete has poor insulation properties and is less effective in preventing heat penetration from external sources. These findings further emphasize the potential benefits of UEO-enhanced foamed concrete over conventional foamed concrete and ordinary concrete without UEO in various construction applications, especially in scenarios where insulation is a key factor. The excellent insulation properties of the developed foamed concrete significantly reduce the demand for heating and cooling energy, which can bring significant cost savings and lower carbon emissions. In addition, the lightweight nature of foamed concrete provides benefits in loading and unloading, transportation, and reducing structural loads, making it a sustainable choice for many construction projects.
[0085] In order to elucidate the microscopic origins of the macroscopic performance changes measured in foamed concrete28, its microstructural surface morphology was investigated in depth and the results are shown in Figure 8(a) to Figure 8(i) The microstructural characteristics of foamed concrete 28, including the pore properties and cement hydration products, were examined because these characteristics are highly correlated with the thermal conductivity and compressive strength of foamed concrete.
[0086] Compared to the microstructural pores observed in the reference foamed concrete as shown in FIG8(a) and the foamed concrete with 2 wt % UEO as shown in FIG8(c), the foamed concrete with 1 wt % UEO is characterized by smaller and more homogeneous pores as shown in FIG8(b). Since uniform pore size distribution is known to improve thermal insulation performance, these unique uniformly generated pores can prevent heat loss, resulting in reduced thermal conductivity. In addition, the uniform internal structure reduces potential material damage due to homogeneity, thereby enhancing mechanical properties. The presence of uniformly dispersed pores can be attributed to the effective dispersion effect facilitated by UEO. Specifically, the sulfite ions in the UEO molecules can be adsorbed onto the surface of the UEO-enhanced foam, thereby repelling each other within the cement paste and resulting in a uniform pore distribution. However, excessive UEO introduces defoamers, which quickly destroy the unbalanced foam system. The adverse effects of UEO are the main cause of foam collapse.
[0087] In addition to the pore characteristics, the formation of cement hydrates on both the boundaries and internal surfaces of the foam-generated pore structure was also examined. Notably, along the foam boundaries, as shown in Figure 8(e), a dense dispersion of ettringite crystals was observed in the concrete sample containing 1 wt% UEO, in contrast to the pure foamed concrete sample shown in Figure 8(d) and the sample with 2 wt% UEO shown in Figure 8(f). This differential growth of cement hydrates indicates that the generated UEO-enhanced foam systems promote the growth of hydrates. This effect may be associated with the increase in hydration reaction sites brought about by the high specific surface area of these foam systems. The accelerated hydration process is another microstructural clue to the enhanced mechanical strength of the developed foamed concrete, which accelerates the hydration process and enhances the mechanical strength of this concrete.
[0088] Regarding the inner surface of the pores generated by the foam, the U10 foam concrete sample exhibits a highly filled microstructure; as shown in Figure 8(h), it has very few pores with a size less than 1 μm and very few cracks, which is different from sample U0 shown in Figure 8(g) and sample U20 shown in Figure 8(i). This observation again implies that appropriate UEO dosage can improve the microstructure of foamed concrete. The mechanism is associated with the dose-dependent nature of UEO. Specifically, due to the high specific surface area of UEO, the addition of low or appropriate concentrations of UEO can increase the hydration reaction sites for the cement hydration process. In addition, UEO can help disperse cement clinker, thereby promoting hydration. However, excessive UEO can destroy the foam system by causing UEO agglomeration, resulting in the appearance of large pores in the foam concrete microstructure. These microstructural explanations prove that the uniformly formed UEO-enhanced pore system and the UEO-promoted hydration process are the microscale roots behind the enhanced macroscopic properties of UEO-enhanced foamed concrete.
[0089] In pursuit of sustainable practices in the environment and construction industry, a low-carbon, lightweight, waste-enhanced LC was developed 3 Concrete formulations that reduce waste and use less raw materials, making them a more sustainable building option. UEO is a potential foam stabilizer, as evidenced by the improved foam stability in the presence of UEO. In addition, incorporating an appropriate amount of upcycled UEO (specifically 1 wt%) into foamed concrete not only enhances its compressive strength by about 15%, but also improves its thermal insulation properties, reducing thermal conductivity by about 16% compared to the reference sample. This enhancement in performance is attributed to the uniform foam structure and promoted cement hydration brought about by the addition of UEO. In addition, using an infrared thermal imaging camera, it has been found that during a two-hour heat penetration test, the UEO-enhanced foamed concrete (U10) recorded temperatures of 20.0°C and 22.9°C at two separate points, which is significantly lower than the 26°C and 31.4°C recorded for ordinary concrete slabs; this demonstrates excellent thermal insulation properties. The development of UEO-enhanced foamed concrete highlights the potential to upcycle waste materials into valuable building materials, thereby contributing to sustainable and deep decarbonization of the construction industry.
[0090] It should be understood that the foregoing merely illustrates examples in which the present invention may be implemented, and that various modifications and / or changes may be made thereto without departing from the spirit of the present invention.
[0091] It should also be understood that certain features of the present invention described in the context of separate embodiments for the sake of clarity may be provided in combination in a single embodiment. Conversely, the various features of the present invention described in the context of a single embodiment for the sake of brevity may also be provided individually or in any suitable sub-combination.
Claims
1. A foamed concrete composition, comprising: Calcined limestone clay cement (LC 3 ), Used engine oil (UEO), Blowing agents, and water.
2. The composition of claim 1, wherein the UEO is 0.5% to 2% by weight of the foam produced.
3. The composition of claim 1, wherein the UEO has a molecular weight of 0.6 g / cm 3 Up to 2.0g / cm 3 density.
4. The composition of claim 1, wherein the foaming agent comprises sodium lauryl sulfate and sodium alcohol ether sulfate.
5. The composition of claim 1, wherein It is 0.3 to 0.
6.
6. The composition of claim 1, wherein the blowing agent has an expansion ratio of 1:30 to 1:
50.
7. The composition of claim 1, wherein the LC 3 Includes ordinary Portland cement, calcined kaolin clay, limestone and gypsum.
8. The composition of claim 7, wherein the weight ratio between the ordinary Portland cement, the calcined kaolin clay, the limestone and the gypsum is about 50:30:15:
5. 9 . Foamed concrete, comprising the foamed concrete composition according to claim 1 .
10. A method for forming a foamed concrete composition, the method comprising: 3 ), waste engine oil (UEO), foaming agent and water are mixed.
11. The method of claim 10, comprising: mixing the blowing agent, the UEO, and the water to form a UEO enhanced foam mixture; The LC 3 Mixed with water to form LC 3 Cement mixtures; and The UEO enhanced foam mixture is mixed with the LC 3 Cement mixture mixing.
12. The method of claim 11, wherein mixing the blowing agent, the UEO, and the water is performed by mixing the blowing agent with a solution of the water and the UEO.
13. The method of claim 12, wherein the UEO is 0.5% to 2% by weight of the foam produced.
14. The method of claim 11, comprising mixing the UEO enhanced foam mixture with the LC 3 The cement mixture is mixed until no visible traces of foam remain.
15. A method of forming foamed concrete, the method comprising forming the foamed concrete composition according to claim 9.
16. The method of claim 15, further comprising curing the foamed concrete composition.
17. The method of claim 16, further comprising: pouring the foamed concrete composition into a mold for curing; as well as The opening of the mold is covered with plastic or aluminum foil during curing.